2011
DOI: 10.1111/j.1750-2659.2011.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple versus single virus respiratory infections: viral load and clinical disease severity in hospitalized children

Abstract: Background Molecular testing for viral pathogens has resulted in increasing detection of multiple viruses in respiratory secretions of ill children. The clinical impact of multiple-virus infections on clinical presentation and outcome is unclear. Objectives To compare clinical characteristics and viral load between children with multiple-virus versus single-virus illnesses. Patients/Methods 893 residual nasal wash samples from children treated for respiratory illness at Children's Hospital, Seattle, from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
222
2
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(259 citation statements)
references
References 28 publications
28
222
2
7
Order By: Relevance
“…In the present study, the differences between infections by single or multiple pathogens were not significant in terms of clinical presentation and severity, with the exception of the higher rate of dyspnea observed in the cases of co-infection. Although some studies found that multiple viral infections were associated with more severe fever, a higher rate of hospitalization and more severe disease (20,32), our findings are in agreement with other studies which have shown that the presence of multiple pathogens was not associated with the severity of the clinical presentation (33,34).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the differences between infections by single or multiple pathogens were not significant in terms of clinical presentation and severity, with the exception of the higher rate of dyspnea observed in the cases of co-infection. Although some studies found that multiple viral infections were associated with more severe fever, a higher rate of hospitalization and more severe disease (20,32), our findings are in agreement with other studies which have shown that the presence of multiple pathogens was not associated with the severity of the clinical presentation (33,34).…”
Section: Discussionsupporting
confidence: 93%
“…Two patients who had association of human bocavirus and RSV were hospitalized. Although some studies reported that patients with multiple viral infections had a more severe course, some other studies reported that the disease course was not affected or a milder course was observed (16,20). It is thought that the disease severity may vary depending on the agent viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Esposito, et al (2013) reported that the difference in LOS between single (6.9 days) and multiple infections (7.1 days) was not significant. Other studies have reported no difference in clinical symptoms, prognosis, or intensive care unit admission rates between single and multiple infections [21][22][23], with some reporting less severe disease in patients with multiple respiratory virus infections [24,25]. These results might be The present study has some limitations.…”
Section: Discussionmentioning
confidence: 57%